LEGAL CULTURE IN THE INFORMATION SOCIETY: TO THE PROBLEM OF UNDERSTANDING THE INFORMATION AND LEGAL CULTURE - Тихомиров, Олександр Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
The purpose is to highlight the peculiarities of the formation of legal culture in an information society, outlining the relevant changes in its modern sense. Research methods: used, in particular, phenomenological, systemic, criterion methods. Results: key information changes in the legal sphere are explained; the inseparability of the relationship between information and legal culture is established; proposed the allocation of information and legal culture as a separate theoretical concept, gave it a definition; outlines its main manifestations in real life and the proposed markers. Discussion: based on the review of the consequences of existing and projected changes in the legal sphere of the information society, the provision on strengthening the influence of information culture on legal culture is argued, which against the background of the general growth of the information sphere information and legal culture as a phenomenon of legal reality and an important basis for further legal development. The article devoted to the new cultural phenomenon problem - information and legal culture and substantiates the need for its understanding. Emphasis is placed on the fact that legal culture is the basis of the legal system, and its high level is a prerequisite for the legal reforms’ effectiveness. At the same time, legal culture is influenced by many society trends, including informatization and globalization. These tendencies form new components in social culture. One of such a component is an information culture. Information culture in the information society significantly impacts other areas of cultural life, including legal culture. As a result, new elements of legal ideology, theoretical constructions and concepts are being formed, as well as new opportunities to search for legal information, interaction between the state and citizens, professional communication of lawyers, etc. Among them are the right for information, information human rights, information delicts and responsibility for them, information security. Based on this, a conclusion about the actual formation and the need for information and legal culture scientific consideration is being made. It is an indicator of the information development of the legal sphere in the information society. The article defines information and legal culture as a quality of the information society legal organization reflection and its individual members, which is achieved by the implementation in real life of an integrated system of legal and information values acquired in the process of world progress. A number of manifestations of information and legal culture in real modern life are being given, its basic markers are offered.